Teaching style, learning motivation, and learning achievement: Do they have significant and positive relationships? - Bagas Adi Atma; Fatun Fatimah Azahra; Ali Mustadi; Colomeischi Aurora Adina (Jurnal Prima Edukasia, 2021)
This study aims at determining whether there is a positive and significant relationship between three variables (teacher teaching style, learning motivation and learning achievement). The subjects in this research were 5th elementary school students in Saptosari sub-district, Gunung Kidul district, with a total of 141 students. This research is correlational quantitative research with data collection using a questionnaire in the form of a research questionnaire containing a scale. The hypothesis in this correlational study used partial correlation analysis and simultaneous regression analysis. The analysis used is data description analysis and multiple linear analysis. The results showed that there was a significant and positive relationship between learning achievement and teaching style got a value of 0.546 with a relative contribution of 23%. Meanwhile, learning motivation and learning achievement got a value of 0.462 with an effective contribution of 9% and the relation between teaching style and learning motivation on learning achievement show an r square value of 0.324 with a total contribution or effective contribution of 32%. Based on the results, it showed that teaching style and learning motivation have a significant and positive relationship with learning achievement.